Pengaruh Net Profit Margin, Current Ratio, dan Debt To Equity Ratio terhadap Return On Assets pada Perusahaan Minyak dan Gas yang Terdaftar di Bursa Efek Indonesia - Taopik Hidayat; Dian Ayu Andriani (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study investigates the determinants of corporate financial performance in the oil and gas sector, a capital-intensive industry characterized by high risk, fluctuating commodity prices, and complex financial structures. Understanding the factors that influence profitability is essential for investors and management, particularly in emerging markets such as Indonesia. Specifically, this research examines the effect of Net Profit Margin (NPM), Current Ratio (CR), and Debt to Equity Ratio (DER) on Return on Assets (ROA) of oil and gas companies listed on the Indonesia Stock Exchange during the 2021–2024 period. A quantitative approach was employed using secondary data collected from the official IDX website. The sample consisted of 9 companies selected through purposive sampling, yielding 36 observations. Data were analyzed using descriptive statistics and multiple linear regression, preceded by classical assumption tests. The findings reveal that partially, Net Profit Margin has a positive and significant effect on ROA. In contrast, the Current Ratio does not have a significant effect, and the Debt to Equity Ratio shows a negative but insignificant effect on ROA. Simultaneously, all independent variables significantly influence ROA. The coefficient of determination (R²) indicates that 96.8% of ROA variation is explained by the model. These results highlight the dominant role of profitability in enhancing firm performance.